Greater Eurasia, Indo-Pacific Region and Russia-ASEAN Relations - E. A. Kanaev (Контуры глобальных трансформаций: политика, экономика, право, 2019)
The article aims to specify the influence of the projects the Greater Eurasia and the Indo-Pacific Region on the prospective relations between Russia and ASEAN. The key component of its novelty is the authors’ original criteria of comparing the two projects: the degree of consolidating agenda of cooperation between their current and prospective participants, the congruence with the East Asia’s – assuming that it will be the economic driver of the forthcoming Greater Eurasia and Indo-Pacific Region – modality of multilateral dialogue and the preconditions for the survivability of both projects in the long-term perspective. Making this comparison, the authors substantiate the view that the Greater Euraya  sian Partnership is far more competitive that the Indo-Pacific Region. Exploring cooperation between Russia and ASEAN through the prism of their forthcoming strategic partnership, the authors offer an original interpretation of the reasons behind the presently insufficient cooperation and its most likely future directions proceeding from the mutual influence of Russia’s and ASEAN’s prospective planning and the emerging global context. In the near future, combating international terrorism and strengthening connectivity will come to the forefront of Russia’s and ASEAN’s priorities, with the focus shifting from Southeast Asia to the Eurasian area. In the authors’ view, if the present trends continue the aftereffects of the Indo-Pacific Region can stimulate downward trends in the Russia-ASEAN relationship. This will be premised upon the decrease in effectiveness of the Asia-Pacific multilateral dialogue platforms, likely Russian-Chinese joint maneuvers in the South China Sea and the necessity to specify, along with lack of impressive results, the essence of the Comprehensive Strategic Partnership between Russia and Vietnam as the foundation for the Russia-ASEAN strategic partnership. In its turn, the Greater Eurasia offers Russia and the association new promising possibilities, among which of particular importance are the development of connectivity narrative in Eurasia and combating international terrorism by means of adopting the ASEAN-led dialogue platforms ARF, ADMM+8 and EAS to the future system of security, cooperation and co-development from Lisbon to Jakarta. The realization of the forthcoming shift from the Asian century to the Eurasian century and the emergence of the Greater Eurasia as the second center in the global politics will allow Russia and the association to expand and diversify their cooperation and, in perspective, to develop it on the self-supporting and self-reproducing basis.